Pathways to environmental activism in four countries: social media, environmental concern, and political efficacy - Boulianne, Shelley; Ohme, Jakob (My University, 2021)
In 2018-9, millions of youth participated in climate-related marches across the globe. This activism reflects youth’s distinctive form of political participation: cause-oriented, expressive, and networked. However, the pathway between environmental concern and environmental activism is complicated in some contexts and for some citizens. This article uses survey data from four countries (Canada, France, the United Kingdom, the United States) gathered in autumn 2019. We focus on the environmental activism of youth and young adults (aged 18–33 years, n = 1574). We find the role of social media is consistent and strong for all environmental activities in all countries; the role of political efficacy depends on activity and country but has a positive role in environmental activism; and environmental concern is a positive and significant correlate of boycotting and signing petitions but a weak predictor of participating in environmental marches. The relationship between environmental concern and environmental marches is distinctive in the United Kingdom. Overall, we find that concern about a social cause does not automatically translate into increased activism related to that cause. Moreover, online social networks, political efficacy, and political context are critical to understanding this mobilization process.
Keywords: environment; youth; social media; political efficacy; cross-national